Terorisme Secara Ontologis Bukan Tindakan yang Benar dan Heroik - Benny Ridwan (Yayasan Bina Darma, 2015)
Terrorism could be define as an act of violence to cause fear in effort to achieve its goal, especially political goal. The violence that occur in nowadays society is like cronical disease that requires respon from the society it self. At certain poin the violence has become vicious circle and become more inherent in human behaviour, and seems to work as systemic behaviour that shackles society. Thus, there is no escape from this situation, the society is in needed for a just social system which has value of sacrality, sanctity, and based on divinity. To enforce such value in practical level leadership is another necessary requirement, in this case a leader who have just quality. To lead is to uphold justice, to guard every member of the society so they could savor their basic right. While at the same time the just leader must ensure and respect freedom and human dignity as a manifestation of social responsibilty awarness.Keywords: Terrorism, Violence, Social Justice